Impacts of recent climate change on terrestrial flora and fauna: Some emerging Australian examples. (20th November 2018) - Hoffmann, Ary A.; Rymer, Paul D.; Byrne, Margaret; Ruthrof, Katinka X.; Whinam, Jennie; McGeoch, Melodie; Bergstrom, Dana M.; Guerin, Greg R.; Sparrow, Ben; Joseph, Leo; Hill, Sarah J.; Andrew, Nigel R.; et al.
Abstract: The effects of anthropogenic climate change on biodiversity are well known for some high‐profile Australian marine systems, including coral bleaching and kelp forest devastation. Less well‐published are the impacts of climate change being observed in terrestrial ecosystems, although ecological models have predicted substantial changes are likely. Detecting and attributing terrestrial changes to anthropogenic factors is difficult due to the ecological importance of extreme conditions, the noisy nature of short‐term data collected with limited resources, and complexities introduced by biotic interactions. Here, we provide a suite of case studies that have considered possible impacts of anthropogenic climate change on Australian terrestrial systems. Our intention is to provide a diverse collection of stories illustrating how Australian flora and fauna are likely responding to direct and indirect effects of anthropogenic climate change. We aim to raise awareness rather than be comprehensive. We include case studies covering canopy dieback in forests, compositional shifts in vegetation, positive feedbacks between climate, vegetation and disturbance regimes, local extinctions in plants, size changes in birds, phenological shifts in reproduction and shifting biotic interactions that threaten communities and endangered species. Some of these changes are direct and clear cut, others are indirect and less clearly connected to climate change; however, all are important in providing insights into the future state of terrestrial ecosystems. We also highlight some of the management issues relevant to conserving terrestrial communities and ecosystems in the face of anthropogenic climate change.